Primordial Sentiment and Political Awareness in Sabah Political Development : A Research in the GE-14 - Eko Prayitno Joko; Zaini Othman; Saat Awang Damit; Ali Akbar Gulasan (2018)
The development of a nation is not only measured by the mechanical aspect that determined by the ability to build the skyscrapers alone, furthermore the organic aspects are symbolized through attitudes, literacy and understanding of an issues. Therefore, Malaysia's aspiration to achieve a developed nation by the year 2020, seems to have been postponed regardless of a marked by the exists of these 'giant' buildings, instead of the existence a critical thinking of the community. The endeavor, which is Malaysia's endless goal, is now regarded as 'thorn in meat' because the way of thinking among the society is determined by the 'feeling' rather than a 'rational' approach. This is ultimately a debate among social scientists toward an influence of the future direction of Malaysia's vision 2especially every general election is held. The belief that, ‘the people are the kings', once again raised an issues of understanding and influences about the ‘primordial sentiment’ and ‘political awareness’ to form a pattern for supporting community especially for the state of Sabah which is considered a fix deposit of the Barisan Nasional. To conceptualization the issues, an effort has been taken by distributing a total of eight thousand questionnaires that included rural and urban areas, in order to see the geo-political orientation of ethnicity as it encompasses indigenous and Non-Bumiputera areas, as well as across religious boundaries. The findings of this research shows that the influence of the ‘primordial sentiment’ has been eroded in determining the pattern of polling in the GE-14, whereas the ‘political awareness’ group were increasingly accepted due to the process of globalization, the advanced of technology and new generation.